The Transformation of Pencak Silat in Perangan Rajamala and Abilawa Prisented by Sudirman Ronggo Darsono. - Hidayatulloh, Muhammad Nabil; Suyanto, Suyanto (Institut Seni Indonesia Yogyakarta, 2025)
Sudirman Ronggo Darsono's sabet perangan has its own characteristics because there is a combination of pencak silat movements. The movement is transformed with the medium of a wayang whose movement has been distilled. Motion transformation research was carried out using qualitative methods, data analysis, and interviews. Sudirman's style of sabet perangan is described specifically about the technique combined with silat movements that it becomes a treasure and insight for readers. The results of the study revealed that several silat movements are transformed to sabet perangan wayang, such as punches, kicks, slams, and evasion.